Efektywność benchmarkingu w doskonaleniu działalności instytucji użyteczności publicznej - Ziębicki, Bernard (Efficiency of Benchmarking in Improving the Activity of Public Utility Organizations, 2006)
The specificity of using of benchmarking in improvement of public activity has been characterised. Multidimensional model as well as criteria and ratios used in the evaluation of benchmarking efficiency in the analysed area have been presented. Description of the results of the research performed by the author, confirming the high efficiency of the benchmarking in improvement of public utility organizations, is the main part of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 401-408